The macroeconomic effects of structural reforms in Latin America and the Caribbean - David, Antonio C.,Komatsuzaki, Takuji,Pienknagura, Samuel (International Monetary Fund, 2020)
This paper estimates the macroeconomic effects of structural reforms in Latin America and the Caribbean (LAC) using the dataset constructed by Alesina and others (2020). We find that large changes in the reform index have positive effects on GDP and employment that reach 2 percent after 5 years. Furthermore, reforms boost investment, exports, imports, and reduce export concentration, in addition to favoring tradable sectors. Nonetheless, the results also indicate that the effects of reforms have not been uniform across different segments of the population. These findings bring to the forefront the need to consider accompanying policies to ensure that reforms promote inclusive growth. Moreover, evidence from country case studies using the synthetic control method point to heterogeneous effects of reforms on income per capita
10.5089/9781513557632.001
Keywords: Graue Literatur; Exports and Imports; Finance: General; Production and Operations Management; Macroeconomics: Consumption; Saving; Production; Employment; and Investment: General (includes Measurement and Data); Macroeconomic Analyses of Economic Development; Economic Growth and Aggregate Productivity: General; Institutions and the Macroeconomy; Labor Contracts; General Financial Markets: General (includes Measurement and Data); Cost; Capital and Total Factor Productivity; Capacity; Trade Policy; International Trade Organizations; Labour; income economics; Finance; International economics; Structural reforms; Employment protection; Commodity markets; Total factor productivity; Trade liberalization; Macrostructural analysis; Labor; Financial markets; Production; International trade; Macroeconomics; Manpower policy; Commodity exchanges; Industrial productivity; Commercial policy; Structural Reforms; Latin America; Macroeconomic Effects